THE ROLE AND IMPACT OF NEOLOGISMS IN MODERN ENGLISH LANGUAGE - Buxalicha Turgunova; Diyora Rustamova (TADQIQOTLAR, 2025)
ABSTRACT This thesis examines the nature, classification, and sociocultural significance of neologisms in modern English. A neologism is generally defined as “ a new word or expression, or a new meaning for an existing word”. The study explores how neologisms emerge, the linguistic processes by which they are formed, and their role in reflecting and influencing contemporary culture. Drawing on the works of prominent linguists – including David Crystal, Jean Aitchison, and Steven Pinker – the research outlines theoretical perspectives on language change and lexical innovation. The findings highlight that English is a dynamic, living language: hundreds of new words enter common usage each year, driven by technological advances, social change, and creative word formation processes. This work also discusses how new words gain acceptance or fall into obscurity, illustrating both the rapid adoption of useful neologisms and the ephemeral nature of others. The conclusion emphasizes that neologisms are both products and agents of sociocultural evolution, serving as a barometer of change in modern English.